2013
DOI: 10.1021/ie4018379
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ethylene succinate)-b-poly(butylene succinate) Multiblock Copolyesters: The Effects of Block Length and Composition on Physical Properties

Abstract: Poly(ethylene succinate)-b-poly(butylene succinate) (PES-b-PBS) multiblock copolymers with different block lengths and compositions were synthesized, and their chemical structure, molecular weights, and polydispersity index of the copolymers were characterized by 1 H NMR and GPC, respectively. The miscibility and crystallization of PES and PBS blocks in the copolymers were investigated by DSC. The results suggested that PES and PBS blocks are miscible in copolymers with shorter block lengths, while they are pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Many SMPs are made of phasesegregated multi-block copolymer structures consisting of hard segments as physical cross-links and so segments as thermoresponsive domains for shape-memory actuation. [37][38][39] The S-AGE described herein is prepared from a one-step, solvent-free bulk polymerization, which, together with its unprecedentedly high strength, excellent performance as a SMP, reprogrammability, and reprocessability, render the new material worthy of further investigations and applications.…”
Section: Mechanical Properties Of S-agementioning
confidence: 99%
“…Many SMPs are made of phasesegregated multi-block copolymer structures consisting of hard segments as physical cross-links and so segments as thermoresponsive domains for shape-memory actuation. [37][38][39] The S-AGE described herein is prepared from a one-step, solvent-free bulk polymerization, which, together with its unprecedentedly high strength, excellent performance as a SMP, reprogrammability, and reprocessability, render the new material worthy of further investigations and applications.…”
Section: Mechanical Properties Of S-agementioning
confidence: 99%
“…Both the glass transition temperatures of these two microdomains increased with the increase of hard polyester weight ratio. Xu et al . found that a block copolymer prepared by a chain‐extension with short length of poly(butylene succinate) (PBS) ( M n = 2060 g mol −1 ) and poly(ethylene succinate) (PES) ( M n = 2370 g mol −1 ) in any proportion had only one glass transition temperature peak, because PBS and PES had good compatibility.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the DSC curve of copolymer-III with the highest M n showed no crystallization peak in its cooling process, but presented a cold crystallization peak concentrated at −20.9 °C in its heating process. The cold crystallization peak is commonly seen in polymers with a low crystallization rate [24], indicating that copolymer-III had the weakest crystallization capability. The broad and small fusion peaks in the heating DSC curves of the block copolymers (Figure 6b) imply that an imperfect crystal structure exists in copolymers, and the imperfect extent increases with M n , as shown by the order of melting temperature ( T m ) of copolymers (Table 1).…”
Section: Resultsmentioning
confidence: 99%